Numerical Analysis of Defects Caused by Thermolysis in an Infinite Cylindrical Ceramic Moulding - Gumel, A. B.; Twizell, E. H. (Universiti Putra Malaysia Press, 1999)
The second-order parabolic (diffusion) equation, which governs the concentration of monomer during pyrolysis of a cylindrical ceramic moulding containing a polymer which degrades to monomer only, is solved: an infinite cylinder is considered. The method of lines is used to transform the partial differential equation into a system of first-order linear ordinary differential equations, the solution of which is seen to satisfy a recurrence relation. The concentration profile at a given time is computed by replacing the matrix exponential terms in this recurrence relation by a high-order Pade approximate. A parallel algorithm using two processors is developed by taking the partial fraction decomposition of the Pade approximate and a (matrix) rational expression in the recurrence relation.